Rich DeCoster letter to Nicholas S. Halmi regarding bird sightings, June 5, 1978 - DeCoster, R. J. (Richard Joseph)et al (1978)
Letter from Rich DeCoster to Nicholas S. Halmi regarding bird sightings, June 5, 1978. A note regarding the sighting of a Yellow Rail at Cone Marsh is underlined. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring, 1978. Epson - sheet feed/flatbed